Optimasi Nilai Ekonomi Produksi Kayu Log pada Industri Mebel Berdasarkan Dimensi dan Efisiensi Produksi - Hemanus J. Suripatty; Petrus Mangambe; Syukriyanto Latif; Suryadi; Everly D.A. Titaley; Wardhana W. Dharsono (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The use of log wood as raw material for furniture and construction industry requires an optimal approach in the dimensions of management and production efficiency to increase economic value. This study aims to analyze the relationship between log wood dimensions (length, width, diameter) with the value of production results based on the percentage of efficiency (60%, 50%, 40%, and 30%). The data used are the results of observations of log wood dimensions from several types (unnamed and with codes: Piton, DL, UP, UD) along with the basic price value of the log. Calculations are carried out to determine the economic value of log wood based on the production efficiency scenario. The results of the study indicate that increasing production efficiency significantly affects the economic value obtained, with the UD log type providing the highest value at all levels of efficiency. This study provides recommendations for wood production optimization strategies based on comparisons of dimensions and efficiency as a basis for decision making in the wood resource-based industry.